Making the leap to teacher: Pre-service residents, faculty, and school mentors taking on action research together in an urban teacher residency program - Emily J. Klein; Monica Taylor; Karina Monteiro; William Romney; Meshelle Scipio; Alex Diaz; Barbara Dunn; Suzanne Poole (Networks: An Online Journal for Teacher Research, 2015)
This article explores what happens when school mentors and university faculty co-facilitate a cycle of action research with pre-service science teacher residents in an urban teacher residency. The voices of all three constituents describe the process of doing action research together in community and its impact on their practice. The pre-service teacher residents narrate their questions, how they explore them, and highlight their findings. They discuss how the use of action research as a methodology deepened and extended their development as critically reflective practitioners. Finally we discuss the implications of the inquiry stance of action research for both the individuals and the schools and districts of which they are a part.